ANALYSIS OF THE LEGIBILITY OF MURABAḤAH WAKALAH FINANCING PRACTICES AT PT. ACEH SHARIA BANK KCP DIPONEGORO: A Case Study Based on Fiqh Muamalah and DSN MUI Fatwa - Amri, Aulil; Linda, Linda (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2022)
Murabaḥah financing is one of the most popular products in Islamic banking. Murabaḥah is defined as the activity of selling an item by confirming the purchase price to the buyer, the buyer pays a higher price than the previous price to make a profit. It can be seen that the essence of murabaḥah is that the bank provides non-money goods, where the bank should buy the goods needed by the customer and then sell them back to the customer at the selling price plus a profit. However, in practice the bank cannot do its own work, that is, it cannot provide the goods required by the customer; rather, the bank only provides funds for the purchase of the goods required through a wakalah contract with the customer in question. This study aims to find answers to the main issues, namely: how is the Fiqh Muamalah review of the practice of murabaḥah wakalah at PT. Bank Aceh Syariah KCP Diponegoro, what is the legitimacy of the practice of murabaḥah wakalah financing according to the DSN MUI fatwa and what is the mechanism for murabaḥah wakalah financing at PT. Bank Aceh Syariah KCP Diponegoro. The type that the author uses in this study is a descriptive analysis method. The data collection method in this study was data obtained from field research through interviews with the parties involved and taking references from a literature review. The results of this study show that there are still sharia principles, the pillars of murabaḥah which are not in accordance with fiqh muamalah and DSN MUI fatwa rules, where in the application of murabaḥah bil wakalah contracts at Bank Aceh Syariah KCP Diponegoro more often use murabaḥah and wakalah contracts in one contract. whereas in theory, the implementation of the wakalah contract must be carried out before the murabaḥah contract is carried out.